2008
DOI: 10.4012/dmj.27.736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber-reinforced composite at the interface on bonding of resin core system to dentin

Abstract: The aim of this study was to evaluate the effect of fiber-reinforced composite (FRC) at the interface on bonding of resin core systems to bovine dentin using different adhesive systems. To this end, the labial surfaces of 60 bovine incisors were ground to obtain flat dentin surfaces and then divided into two groups according to the adhesive system used: total-etching (Solobond Plus) versus self-etching (Clearfil SE Bond). Resin core systems were bonded to tooth structure either without or with a FRC layer (eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Leveraging the advances in adhesive bonding technology, the conservative approach of minimally invasive dentistry allows the esthetics and function of anterior teeth to be restored with adhesive fixed partial dentures. Fueled by increasing interest in metal-free esthetic dentistry, glass fiber-reinforced composite (FRC) has been used in myriad dental applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Of particular interest to this paper are the adhesive fixed partial dentures (AFPDs), which have been favorably reported because of their good clinical performance [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the advances in adhesive bonding technology, the conservative approach of minimally invasive dentistry allows the esthetics and function of anterior teeth to be restored with adhesive fixed partial dentures. Fueled by increasing interest in metal-free esthetic dentistry, glass fiber-reinforced composite (FRC) has been used in myriad dental applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Of particular interest to this paper are the adhesive fixed partial dentures (AFPDs), which have been favorably reported because of their good clinical performance [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Meiers et al 29 found that a woven polyethylene FRC (Connect), placed at the interface of the composite to the etched/adhesively treated enamel surface significantly increased the SBS compared with a composite with no fiber reinforcement control and 3 other types of FRC products (Ribbond, Splint-It Unidirectional, and Splint-It Woven). Çekiç-Nagas et al 17 investigated the effect of fiber addition (Everstick Net) on bonding using different resin core adhesive systems with bovine dentin. They determined that the fibers used caused a significant increase in the SBS and changes in the failure type.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported greater adhesive failure in specimens with lower bonding resistance, and that as systems' low adhesive resistance progressed to high resistance, there was a greater possible correlation between bonding resistance and fracture type, based on increased mixed and cohesive fracture modes. 17,32 Cohesive and mixed failure levels of 50% (for enamel) and 60% (for dentin) were obtained for the CT FRCs, and 40% (for enamel) and 30% (for dentin) for the ES FRCs, all of which had high SBS values. The results of this study are in accordance with previous studies showing changes in fracture patterns due to the addition of an FRC to the tooth/composite interface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restoratif materyallerin mine ve dentine bağlanma dayanımlarını loop (ilmik), bıçak sırtı veya çentikli uçlar kullanarak değerlendiren bu test yöntemi, diş yüzeyi ile restorasyon arasındaki bağlantıyı ayıracak şekilde bıçak sırtı şeklinde bir aparat yardımı ile uygulanmaktadır. 10,11 Aparatın kesici ucunun hızı 0,45 ve 1,05 mm/dk arasında olmalı ve kesici ucun bağlanma yüzeyine en yakın şekilde konumlandırılması gerektiği bildirilmiştir. 12 Bu in-vitro çalışmanın amacı; laminate veneer yapımında kullanılan dört farklı kompozit rezin materyalinin makaslama dayanım dirençleri açısından karşılaştırılarak değer-lendirilmesidir.…”
Section: Introductionunclassified